EXPERIMENTAL SUBSTANTIATION OF POLYVALENT ORAL GEL USAGE FOR PREVENTION AND TREATMENT OF PERIODONTAL INFLAMMATION - V. G. Stolyar; A. V. Borysenko; A. P. Levitsky (Bogomolets National Medical University, 2015)
Summary. During the dental implantation quite often develope an inflammatory process in the bone tissue around the implant. For the prevention and treatment of the inflammatory process proposed oral gel. It consists of osteovit, propolis tincture, Metrogil-Denta, chlorhexidine and silicon dioxide. This composition has antibacterial and anti-inflammatory effect. At experimental conditions antiinflammatory effect of this composition on the inflammatory process in the periodontium were studied. Experiments were performed on 32 Wistar rats which were administered with food prednisolone at 5 mg/kg for 14 days. Part of the rats received daily applications of oral gel containing propolis, osteovit, metrogil, chlorhexidine, silicon dioxide. As a comparison, the drug ointment Mefenat was used. The results were studied using histologic and biochemical techniques. The following parameters were investigated: the degree of atrophy of the alveolar bone, the level of markers of inflammation in the gingiva (MDA, elastase), microbial contamination (urease), nonspecific immunity (lysozyme), antioxidant defenses (catalase), permeability of histohematic barriers (hyaluronic acid). Prednisolone administration with food causes the development of inflammation in periodontal tissue of rats. After the application of drug compositions pathohistological examination revealed the presence of anti-inflammatory effect of the composition. This medicamental composition in rats with prednisolone periodontitis reduces the activity of acid phosphatase, increases the ratio of alkaline phosphatase/acid phosphatase and mineralization, reduces the degree of atrophy of the alveolar bone. The experimental pathohistological and biochemical investigations revealed the presence of anti-inflammatory drug action in the proposed medicamental composition.